(untitled) (Acta Scientiarum. Education, 2011)
Considering that the use of Augmentative and Alternative Communication Systems (AACS) has been recommended for children who are severely impaired in their development of communicative abilities, it may be assumed that caregivers’ attitudes toward AACS would be driven by children’s degree of cognitive and linguistic impairments. To verify this, 40 dyads of children with cerebral palsy and their primary caregivers participated in this study evaluating children’s degree of cognitive and linguistic impairments through the use of Battelle’s questionnaire, and the caregivers’ attitudes toward AACS by means of a Likert scale containing 15 items. Results showed that the provider’s most negative attitudes toward the use of AACS were found among those caring for children with the most severe impairments.